2022
DOI: 10.3390/antiox11101926
|View full text |Cite
|
Sign up to set email alerts
|

NCOA4 Regulates Iron Recycling and Responds to Hepcidin Activity and Lipopolysaccharide in Macrophages

Abstract: Macrophages, via erythrophagocytosis, recycle iron from effete erythrocytes to newly developing red blood cells. Conversion of potentially cytotoxic levels of iron from its heme into nonheme form during iron recycling is safely accomplished via coordinated regulations of cellular iron transport and homeostasis. Herein, we demonstrate the roles and regulation of NCOA4 (nuclear receptor coactivator 4)-mediated ferritinophagy in macrophages after erythrophagocytosis using the mouse macrophage cell line J774 cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The cells were washed twice with ice-cold PBS containing 10 mM ethylenediaminetetraacetic acid (EDTA) and transferred to acid-washed tubes at the third washing step. Frozen pellets of a known number of cells were processed and analyzed at the University of Nebraska for quantitative measurements of mineral contents using inductively coupled plasma mass spectrometry (ICP-MS), as previously described [ 24 ]. Metal contents were normalized to total protein contents determined by the bicinchoninic acid (BCA) assays (Thermo Scientific, Waltham, MA, USA; #23225), cell counts, or phosphorous levels of each sample.…”
Section: Methodsmentioning
confidence: 99%
“…The cells were washed twice with ice-cold PBS containing 10 mM ethylenediaminetetraacetic acid (EDTA) and transferred to acid-washed tubes at the third washing step. Frozen pellets of a known number of cells were processed and analyzed at the University of Nebraska for quantitative measurements of mineral contents using inductively coupled plasma mass spectrometry (ICP-MS), as previously described [ 24 ]. Metal contents were normalized to total protein contents determined by the bicinchoninic acid (BCA) assays (Thermo Scientific, Waltham, MA, USA; #23225), cell counts, or phosphorous levels of each sample.…”
Section: Methodsmentioning
confidence: 99%
“…Based on mouse studies, minihepcidin can mimic the biological function of natural hepcidin and block iron export through ferroportin, making it a potential drug candidate for treatment or prevention of iron overload. Minihepcidin has been used in murine studies on iron absorption and iron homeostasis ( Guggisberg et al, 2022 ; Hanudel et al, 2022 ) and can be used in conjunction with tracer studies to produce rapid and complete inhibition of ferroportin-mediated iron efflux.…”
Section: Capture Of Dietary Iron In Intestinal Epitheliummentioning
confidence: 99%
“…In the first place, NCOA4 plays a role in cancer therapy. Studies have shown that lipopolysaccharide (LPS) can regulate ferritin conversion by inhibiting NCOA4 as a therapeutic target for cancer [ 83 ]. Powdered tetrandrine citrate (TetC), a novel highly water-soluble powdered cycloheximide salt, has strong anticancer activity not only in chronic myeloid leukemia, but also in breast cancer cells by inhibiting GPX4 expression and activation of NCOA4 to promote ferritinophagy in cancer cells inducing ferrogenic cell death [ 80 ].…”
Section: Main Textmentioning
confidence: 99%